The evolutionary history of Trichoptera (Insecta): A case of successful adaptation to life in freshwater. (8th May 2013) - MALM, TOBIAS; JOHANSON, KJELL ARNE; WAHLBERG, NIKLAS
Abstract The insect order Trichoptera (caddisflies) forms the second most species‐rich monophyletic group of animals in freshwater. So far, several attempts have been made to elucidate its evolutionary history with both morphological and molecular data. However, none have attempted to analyse the time frame for its diversification. The order is divided into three suborders – Annulipalpia, Integripalpia and 'Spicipalpia'. Historically, the most problematic taxon to place within the order is 'Spicipalpia', whose larvae do not build traditional cases or filtering nets like the majority of the caddisflies. They have previously been proposed to be the sister group of all other Trichoptera or more advanced within the order, with equivocal monophyly and with different interordinal placements among various studies. In order to resolve the evolutionary history of the caddisflies as well as timing their diversification, we utilized fragments of three nuclear (carbamoylphosphate synthethase, isocitrate dehydrogenase and RNA polymerase II) and one mitochondrial (cytochrome oxidase I) protein coding genes, with 16 fossil trichopteran taxa used for time calibration. The 'spicipalpian' families are recovered as ancestral to all other caddisflies, though paraphyletic. We recover stable relationships among most families and superfamilies, resolving many previously unrecognized phylogenetic affinities amongst extant families. The origin of Trichoptera is estimated to be around 234 Ma, i.e. Middle – Late Triassic.